Sociology and health : an introduction - Morrall, Peter. 4 0 16; Morrall, Peter; 5 (London : Routledge, 2009)
This introductory text provides students and health practitioners with the foundations of a sociological understanding of health issues. Written for anyone who is interested in health and disease in contemporary global society, this book engages the reader to act upon their occupational and moral responsibilities. It explains the key sociological theories and debates with humour and imagination in a way that will encourage an inquisitive and reflective approach on the part of any student who engages with the text. With individual chapters covering sociology, health, science, power, medicalisation, madness happiness, sex, violence and death, Sociology and Health is organized so that the student moves through sociological approaches and themes which constantly recur in the experience of healthcare. Students will find this a readable and controversial text which covers the ground they need to know in a thought-provoking way. Lecturers will find it a helpful text for generating discussion in tutorials and seminars. There are summaries at the end of each chapter, suggestions for further reading and ideas for the reader.--Jacket.
Sociology -- Health -- Science -- Power -- Medicalisation -- Madness -- Misery -- Sex -- Death.
Revised edition of: Sociology and nursing / Peter Morrall. 2001.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Social aspects. -- Social medicine.;Sociology.;Nursing;Sociology, Medical. -- 20; 20; 2